Efektifitas Pembelajaran The Power of Two Berbantuan ICT Untuk Meningkatkan Kemampuan Pemahaman dan Pemecahan Masalah Matematis Siswa SMP - Nora Susilowaty (LPPM Universitas Advent Indonesia, 2023)
A good learning strategy can improve students' abilities. This study aims to determine the effect of ICT-assisted the power of two learning on improving students' mathematical understanding and problem solving abilities, to find out whether there is a correlation or relationship between students' understanding abilities and students' mathematical problem solving abilities, and to determine student responses to learning the power of two ICT-assisted. This study used a one group pretest-posttest design with a purposive sampling technique. This study used one class, namely 24 students from class VII SMP Adventist Parongpong in West Bandung. The instruments used in this study were tests describing students' mathematical understanding and problem solving abilities on the subject of triangles and student response questionnaires. The results of this study are: an increase in the ability to understand and solve mathematical problems of students who receive ICT-assisted the power of two learning is in the moderate category, after being given treatment the ability to understand and solve mathematical problems of students is better than before it is given, there is a strong correlation between understanding abilities and mathematical problem solving abilities, students' responses to the learning given are very satisfied and give positive responses.